Familial ovarian cancer. - Elit, L. (2001)
OBJECTIVE: To assist family physicians in evaluating patients' risk for hereditary ovarian cancer and to review strategies for preventing ovarian cancer. QUALITY OF EVIDENCE: The MEDLINE, EMBASE, CANCERLIT, and CINAHL databases were searched from 1970 to 1999 using key words related to hereditary ovarian cancer, screening, oral contraceptives, prophylactic oophorectomy, cancer worriers, satisfaction, and perceived risk. Recommendations in this paper are based on evidence from case-control and cohort studies and, where appropriate, consensus conferences. MAIN MESSAGE: Of all women who present with ovarian cancer, 20% have a family history of ovarian cancer and 8% carry a BRCA 1 or BRCA 2 mutation. Women who carry a BRCA 1 mutation have a 63% lifetime risk of developing ovarian cancer, and women who carry a BRCA 2 mutation have a 27% lifetime risk of developing ovarian cancer. Preventive strategies include screening (level 3 evidence for postmenopausal women and level 5 evidence for women with a family history of ovarian cancer), use of oral contraceptives (level 3 evidence for the general population and for mutation carriers), and prophylactic oophorectomy (level 3 evidence in first-degree relatives of patients with breast or ovarian cancer). CONCLUSION: Women who have a family history of ovarian cancer should be offered genetic counseling and discussion of various preventive strategies for minimizing their risk.